2011
DOI: 10.3354/meps09453
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycles and spring blooms in phytoplankton: don’t abandon Sverdrup completely

Abstract: The critical-depth model for the onset of the spring phytoplankton bloom in the North Atlantic has recently been called into question by several researchers. The critical-depth model considers that the spring bloom starts when the mixed layer shoals to become shallower than a critical depth. Satellite and in situ measurements of chlorophyll are used here to show that the critical-depth model is indeed flawed. It is shown that the critical-depth model does not apply in the spring because the basic assumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
125
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 24 publications
16
125
1
1
Order By: Relevance
“…Our observations and those reported above indicate instead that phytoplankton blooms may be diverse in terms of patterns and formation mechanisms (e.g. Townsend et al, 1992;Behrenfeld, 2010;Chiswell, 2011). High phytoplankton biomass in the absence of thermal stratification could be explained by (1) the close-to-the-surface bottom, which keeps phytoplankton in layer that is always well illuminated , (2) sustained periods of calm weather during which vertical mixing would be weak (Townsend et al, 1994), (3) rate of phytoplankton photoacclimation faster than vertical mixing (Morán and Estrada, 2005), and (4) decoupling between phytoplankton growth and grazing, which would make the loss term (grazing) smaller than the gain (growth) (Behrenfeld, 2010;Herrmann et al, 2013).…”
Section: Specific Aspects Of the Phytoplankton Bloom In The Bay Of Calvisupporting
confidence: 45%
“…Our observations and those reported above indicate instead that phytoplankton blooms may be diverse in terms of patterns and formation mechanisms (e.g. Townsend et al, 1992;Behrenfeld, 2010;Chiswell, 2011). High phytoplankton biomass in the absence of thermal stratification could be explained by (1) the close-to-the-surface bottom, which keeps phytoplankton in layer that is always well illuminated , (2) sustained periods of calm weather during which vertical mixing would be weak (Townsend et al, 1994), (3) rate of phytoplankton photoacclimation faster than vertical mixing (Morán and Estrada, 2005), and (4) decoupling between phytoplankton growth and grazing, which would make the loss term (grazing) smaller than the gain (growth) (Behrenfeld, 2010;Herrmann et al, 2013).…”
Section: Specific Aspects Of the Phytoplankton Bloom In The Bay Of Calvisupporting
confidence: 45%
“…Outside the eddies, D NO 3 is determined by nitrate biological assimilation during the spring-summer-autumn period, and a D NO 3 near the beginning of winter EZD is expected for a stratified ocean. If, during winter, W-MLD is lower than D NO 3 , there is no new supply of nitrate into the photic zone and the oligotrophic status of the system will increase, even if primary production may temporarily increase because of increasing irradiance following the winter solstice (Behrenfeld, 2010;Chiswell, 2011 2. Inside an eddy core formed during winter, water less dense and exhausted in nutrients accumulates.…”
Section: T Moutin and L Prieur: Influence Of Anticyclonic Eddies Onmentioning
confidence: 99%
“…Similarly, within polynyas there is a narrow opportunity for phytoplankton growth, the timing of which plays an important role in both biogeochemical cycles (Smith Jr. and Barber, 2007) and biological production (Arrigo and van Dijken, 2003;Ainley et al, 2010). However, while studies have suggested that the timing of sea ice retreat is synchronized with the timing of the phytoplankton bloom, other factors such as wind forcing (Chiswell, 2011), thermal convection (Ferrari et al, 2014) and iron availability (Boyd et al, 2007, and references therein) play important roles as well.…”
mentioning
confidence: 99%